UK‐US Trade Relations and 'Global Britain'. Issue 4 (6th November 2021) - Heron, Tony; Siles‐Brügge, Gabriel
Abstract: A UK‐US free trade agreement has consistently been presented as the main prize from the UK's much touted post‐Brexit trade policy independence. The UK Prime Minister's admission that this was not going to be realised any time soon may have surprised media pundits, but it merely confirmed what had become increasingly apparent since the referendum: that a free trade agreement with the US was a long shot. Taken together with the short‐lived suggestion of the UK joining the United States‐Mexico‐Canada Agreement (USMCA), we argue that it is the desire to perform 'independence' from the European Union rather than policy content which is driving the UK's trade strategy.